PERILAKU PENGGUNA AIR SUNGAI DENGAN KELUHAN KESEHATAN KULIT PADA MASYARAKAT SEKITAR SUNGAI PANGAMBANGAN BANJARMASIN - Fahrurazi Fahrurazi; Yeni Riza; Erwin Ernadi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2018)
The results of river water quality monitoring from 2013 to 2015 resulted that the Martapura River and Barito River included in severe pollutant status. The purpose of this research is to know the behavior of river water users and the utilization of health services with complaints of skin health by the community around the Banjarmasin mining river. The target of this research is expected to be continued to be dedication to the community around the Banjarmasin Pangambangan river so that people can improve their knowledge, attitude and actions towards healthy living and able to utilize health services, especially the nearest public health center. The research method used is descriptive with cross sectional approach. The sample is done by purposive sampling that is sampling by not giving equal opportunity from every member of population. The instrument in this research is using questionnaire with interview technique. Analysis of this data using Chi Square statistical test with the help of computerization Mean value (a) 0.05 with confidence value 0.95. The results of the research on behavioral variables that include: knowledge, attitude and action show that there is no relationship between knowledge about the use of river water with skin health complaints (p-Value = 0.130). There is no correlation between attitude toward river water usage with skin health complaint (p-Value = 1,000). There is no correlation between the action in the use of river water with skin health complaint (p-Value = 0,130) Most people do not experience skin health complaints that is as much 89 people (96,7%) .Suggestions that can be given that is for responder increase awareness in maintaining and conserving river water, the awareness of the community to behave healthy life with the basic provisions of environmental management.